Towards an Objective-Driven System of Smart Labor Migration Management - Robert Holzmann; Yann Pouget (Institute for the Study of Labor (IZA), 2010)
This policy note offers motivation as well as game plan how to achieve a coherent and mutually beneficial labor migration system. It argues that migrant workers may importantly contribute to economic growth and development both in sending and receiving countries if they find the enabling conditions. To achieve a potential win-win-win situation requires (i) a sustainable migration management system that takes into account the interests of the various stakeholders involved; (ii) a clear identification and articulation of objectives and interests in migration by the key stakeholders based on a common conceptual framework on migration and development: (iii) regional and bilateral coordination mechanisms to balance these not necessarily converging objectives and reach comprise under labor agreements and policies; and (iv) evidence-based effective polices and public and private sector interventions to achieve the objectives that are known and applied at the level of sending, receiving, returning and circulation.
Keywords: F22; J1; O19; 330; migration management; economic development; monitoring and evaluation; Arbeitsmigranten; Migrationspolitik; Wirtschaftspolitisches Ziel; Entwicklung; Welt